Perubahan Pola Tanam dari Bertani Jagung ke Sawah Petani Masyarakat Wakumoro Kecamatan Parigi Kabupaten Muna - Lufty Alfirah; Hartini Hartini (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
This study aims to determine changes in cropping patterns and factors that influence changes in cropping patterns carried out by farmers in Wakumoro Village, Parigi District. The method used is ethnography. Data collection was carried out using observation techniques and in-depth interviews as well as purposive sampling informant selection techniques. The data obtained were analyzed descriptively. That the change in cropping patterns from corn to rice carried out by the farmers in Wakumoro Village is an option for improving their economy as traditional farmers, where the income from rice yields is quite promising, when compared to corn, the superiority of rice is very clear compared to corn, even though corn has abundant yields for farmers in Wakumoro Village but the selling price is not comparable and not what farmers expect, where corn has prices that tend to be cheaper than rice, besides that abundant corn yields are one of the obstacles for farmers This is due to the large corn yields which reach tons in one harvest, there is no reservoir and all will not be sold.